Immunity and clinical efficacy of an inactivated enterovirus 71 vaccine in healthy Chinese children: A report of further observations - Longding, Liu; Zhaojun, Mo; Zhenglun, Liang; Ying, Zhang; Rongcheng, Li; Kien, Chai Ong; Kum, Thong Wong; Erxia, Yang; Yanchun, Che; Jingjing, Wang; Chenghong, Dong; Min, Feng; et al. (BioMed Central Ltd., 2015)
Background: To investigate the long-term effects on immunity of an inactivated enterovirus 71 (EV71) vaccine and its protective efficacy. Methods: A sub-cohort of 1,100 volunteers from Guangxi Province in China was eligible for enrolment and randomly administered either the EV71 vaccine or a placebo on days 0 and 28 in a phase III clinical trial and then observed for the following 2 years with approval by an independent ethics committee of Guangxi Zhuang Autonomous Region, China. Serum samples from the 350 participants who provided a full series of blood samples (at all the sampling points) within the 2-year period were collected. Vaccine-induced immune effects, including the neutralizing antibody titres and cross-protection against different genotypes of EV71, were examined. This study also evaluated the protective efficacy of this vaccine based upon clinical diagnosis. Results: This sub-cohort showed a >60 % drop-out rate over 2 years. The seroconversion rates among the 161 immunized subjects remained >95 % at the end of study. The geometric mean titres of neutralizing antibodies (anti-genotype C4) 360 days after vaccination in 350 subjects were 81.0 (subjects aged 6-11 months), 98.4 (12-23 months), 95.0 (24-35 months), and 81.8 (36-71 months). These titres subsequently increased to 423.1, 659.0, 545.0, and 321.9, respectively, at 540 days post-immunization (d.p.i.), and similar levels were maintained at 720 d.p.i. Higher IFN-γ/IL-4-specific responses to the C4 genotype of EV71 and cross-neutralization reactivity against major EV71 genotype strains were observed in the vaccine group compared to those in the placebo group. Five EV71-infected subjects were observed in the placebo-treated control group and none in the vaccine-immunized group in per-protocol analysis. Conclusion: These results are consistent with the induction of dynamic immune responses and protective efficacy of the vaccine against most circulating EV71 strains. Trial registration number: Clinicaltrials.gov, NCT01569581 , Trial registration date: March 2012 © 2015 Liu et al.